Slicer method comparison using open-source 3D printer - Mohd Ariffin, M K A; Sukindar, Nor Aiman; Baharudin, B.T. H T; Jaafar, C N A; Ismail, M I S (IOP Publishing, 2018)
Open-source 3D printer has been one of the popular choices in fabricating 3D models. This technology is easily accessible and low in cost. However, several studies have been made to improve the performance of this low-cost technology in term of the accuracy of the parts finish. This study is focusing on the selection of slicer mode between CuraEngine and Slic3r. The effect on this slicer has been observe in terms of accuracy and surface visualization. The result shows that if the accuracy is the top priority, CuraEngine is the better option to use as contribute more accuracy as well as less filament is needed compared to the Slice3r. Slice3r may be very useful for complicated parts such as hanging structure due to excessive material which act as support material. The study provides basic platform for the user to have an idea which option to be used in fabricating 3D model.